Electromagnetic Non-Contacting Position Estimation of a Centimetre-Scale Robot. Issue 37 (2022) - Pushpalayam, N.; Alexander, L.; Rajamani, R.
Abstract: This paper develops an electromagnet-based position estimation system for a cm-scale robot with two degrees of freedom. The orientation of an external electromagnet is actively controlled in realtime to maximize the magnetic field magnitude at the robot. This results in a monotonic relationship between the magnetic field magnitude and radial distance leading to a simple and robust position estimation system. The radial distance is then estimated using an asymptotically stable nonlinear observer designed using a linear matrix inequality. The analytical principles of the estimation system are first presented using key technical lemmas and proofs. Experimental results are then presented on the verification of the analytical principles and on the performance of the position estimation system.